Benjamin-Ono Equation on a Half-Line - Nakao Hayashi; Elena I. Kaikina (International Journal of Mathematics and Mathematical Sciences)
We consider the initial-boundary value problem for Benjamin-Ono equation on a half-line. We study traditionally important problems of the theory of nonlinear partial differential equations, such as global in time existence of solutions to the initial-boundary value problem and the asymptotic behavior of solutions for large time.